Seroprevalence of Peste des Petits Ruminant Virus specific antibody in goats in different regions of Bangladesh - Islam, Md. Mahbubul; Hasan, Md. Ashraful; Yousuf, Md. Abu; Islam, Umme Kumkum; Shawan, Mohammad Mahfuz Ali Khan; Islam, Mohammad Rafiqul (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: The study was undertaken with an objective to determine the seroprevalence of Peste des Petits Ruminants (PPR) in goats of different age groups. Materials and methods: A total of 606 goats (414 vaccinated and 192 unvaccinated) were randomly selected from Rajshahi, Sirajganj and Gazipur districts. The goats were categorized into different age gropus; (i) 0-6 months, (ii) 12-24 months, and (iii) >24 months. Blood samples were collected from the goats and sera were prepared. The sera were examined for the presence of antibodies against PPR virus (PPRV) by competitive enzyme linked immunosorbent assay (c-ELISA). Results: In the unvaccinated goats, overall seroprevalence was 8.70% (n=36/414). The highest seroprevalence was recorded in Rajshahi (28.57%; n=18/63) which was followed by Gazipur (16%; n=12/75) and Sirajganj (2.17%; n=6/276). The age-based overall seroprevalence in the unvaccinated samples from 0-6 months age group was 9.43% (n=15/159). Similarly, 12-24 and >24 months age groups of goats revealed the presence of 6% (n=9/150) and 11.43% (n=12/105) seroprevalence against PPRV. Of the vaccinated samples, overall 76.04% (n=146/192) were seropositive against PPRV. Within the age group of 0-6 months, vaccinated samples had the highest seroprevalence (80.25%; n=65/81) as compared to 12-24 (70.83%; n=34/48) and >24 months (74.60%; n=47/63) age groups of goats, respectively. Conclusion: The seroprevalence in the unvaccinated samples indicates that PPRV is circulating in Bangladesh which is inducing to produce natural antibody in goats. This study also states that the field level vaccination against PPRV could give protection to the goats. http://doi.org/10.5455/javar.2016.c140